EFFICIENCY OF THE OFFERED WAY OF OBJECTIVE ASSESSMENT OF DEGREE OF THE PROLAPSE OF THE PELVIC BOTTOM AT WOMEN - Мозес, Вадим Гельевич; Короткевич, Олеся Сергеевна (Mother and Baby in Kuzbass, 2017)
The aim of the research: to determine the effectiveness of the author’s method of objective evaluation of pelvic floor prolapse in women. Materials and methods: assessment of the degree of pelvic floor prolapse by the author’s method in comparison with visual assessment according to Baden-Wolker classification. Results: an objective evaluation of pelvic floor prolapse by the method of Baden-Wolker and by the author’s method showed comparable data, revealing the prevalence of the first and second degree of the disease in the examined women and the absence of a correlation relationship between these methods. It was decided to introduce into practice a common denominator that would allow an adequate assessment of the varying severity of pelvic organ prolapse with a narrowing of the range of quantitative guidelines. Conclusion: the conducted research allowed to establish that the proposed author’s method combines the simplicity and correspondence with the existing, more complex and time-consuming methods of objective evaluation of the degree of pelvic floor prolapse in women.